MoTe2/MoSe2 vdW Schottky photodetector for polarized photodetection - Peng Gao; Lei Liu; Yanbo Tang; Shuo Liu; Tinghao Wang; Mengru Zhang; Bo Li; Mianzeng Zhong; Da Wan; Chunlan Wang; Yingfen Wei; Lei Liao; et al. (Chip)
Polarized photodetectors can achieve higher resolution and gather more detailed surface information about imaging targets in complex environments by identifying light polarization. However, it still remains challenging to achieve both a high polarization ratio (>10) and a fast response time. In this work, we demonstrated a gate-tunable polarized photodetectors utilizing 2D semiconductor MoSe2 and semimetal 1T′-MoTe2. Leveraging the anisotropic in-plane structure of 1T′-MoTe2, our device exhibits excellent polarization-sensitive photodetection with a polarization ratio as high as 15.48. The photodetector shows a rapid rise and decay time of 362 μs and 480 μs under 405 nm light illumination with a broad spectral photoresponse spanning 265 to 880 nm. Key performance metrics include a high responsivity of 130.89 mA/W and a specific detectivity of 1.15 × 1011 Jones. By combining the photodetector's fast imaging capability with a mechanistic learning approach, precise image recognition was achieved. This work opens new avenues for developing two-dimensional material-based systems for polarized light imaging and image identification.